Zambia : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Zambia. (IMF Staff Country Reports; Country Report ;, 2008)
The Zambian economy has performed well owing to its strong macroeconomic policies, high copper export prices, and extensive debt relief. Executive Directors encouraged the authorities to reduce poverty and attain the Millennium Development Goals (MDGs) under the Fifth National Development Plan (FNDP), and emphasized to authorities to improve budget execution and create fiscal space for increased spending on infrastructure and social sectors. They commended the tight monetary policy and fiscal stances, revenue reforms, and efforts to strengthen debt management. They welcomed financial sector reforms and also the trade regime to accelerate export development.